Does myringosclerosis affect the success of butterfly myringoplasty? - Akyigit, Abdulvahap; Karlidag, Turgut; Eroglu, Orkun; Akin, Fatma Ucak; Kaygusuz, Irfan (Elsevier Sci Ltd, 2023)
Objectives: Butterfly inlay myringoplasty is a simple and practical surgical technique used in the repair of tympanic membrane perforation offering good outcomes in terms of hearing. The present study evaluates the effects of myringosclerosis on the success of surgery by reviewing demographic data, perforation size and hearing outcomes of patients undergoing endoscopic inlay butterfly myringoplasty due to chronic otitis media. Methods: The study included 75 patients who underwent endoscopic inlay butterfly myringoplasty with the diagnosis of chronic suppurative otitis media in the Department of Otorhinolaryngology at Firat University Faculty of Medicine between March 2018 and July 2021. The patients were divided into three groups as the following. Group I: Patients without a myringosclerotic focus in the neighborhood of tympanic membrane perforation, Group II: Patients with a less than 50% myringosclerotic focus in the neighborhood of tympanic membrane, and Group III: Patients with a more than 50% myringosclerotic focus in the neighborhood of tympanic membrane. Results: The comparison of all preoperative and postoperative parameters and the reduction in air-bone gap between the groups did not show statistically significant difference (p>0.05). The comparison of air-bone gaps between preoperative and postoperative measurements showed a statistically significant difference in all groups (p<0.05). The grafting success rate was 100% in Group I, 96.4% in Group II, and 95.6% in Group III. The mean operation time was 28.57 +/- 2.54 min in Group I, 32.14 +/- 2.44 min in Group II, and 30.69 +/- 3.43 in Group III; there was a statistically significant difference only between Group I and Group II (p = 0.001). Conclusions: The graft success rate and hearing gain in patients with myringosclerosis were similar to those in patients without myringosclerosis. Therefore, butterfly inlay myringoplasty is applicable to patients with chronic otitis media regardless of the presence or absence of myringosclerosis.
Keywords: Cartilage; Myringoplasty; Myringosclerosis